Reproductive Outcome following Hysteroscopic Monopolar Metroplasty: An Analysis of 203 Cases - Ensieh Shahrokh Tehraninejad; Firouzeh Ghaffari; Nadia Jahangiri; Mansoureh Oroomiechiha; Mohammad Reza Akhoond; Elham Aziminekoo (International Journal of Fertility and Sterility, 2013)
Background: The aim of this study was to evaluate the reproductive outcome of women with history of infertility or recurrent miscarriage following hysteroscopic septum resection. Materials and Methods: This was a retrospective descriptive study performed on 263 patients, among whom 248 patients were infertile (79% with primary infertility and 21% with secondary infertility) and 15 patients presented with histories of recurrent miscarriage (three or more miscarriages) between 2005 and 2009. All participants underwent hysteroscopic septum resection using monopolar knife electrode. The main outcome measure was reproductive outcome after hysteroscopic metroplasty. Results: The septum was completely removed during the first hysteroscopy in 242 (92%) patients. A residual septum was seen in 21 (8%) patients who required a second sitting of surgery. Three cases were complicated by minor perforations which required no further interventions. One operation complicated with bleeding which was controlled by a Foley catheter. There were no cases of postoperative Asherman’s syndrome. Postoperatively, out of 263 patients, outcomes of 203 individuals were analyzed. According to the results, the miscarriage rate reduced significantly from 20.2 to 4.9%. Postoperative ectopic pregnancy rate and preterm labor were lower than prior to septum resection. Term deliveries increased significantly from 2.5 to 33.5%. Conclusion: Hysteroscopic septum resection is a safe and effective method for patients with history of infertility or recurrent miscarriage.